3D Printable, Modified Trephine Designs for Consistent Anterior Lamellar Keratectomy Wounds in Rabbits. (3rd August 2021) - Chen, Fang; Buickians, David; Le, Peter; Xia, Xin; Montague-Alamin, Spencer Q.; Blanco Varela, Ignacio Blanco; Mundy, David C.; Logan, Caitlin M.; Myung, David
ABSTRACT: Purpose: Our goal is to develop a low-cost tool that can be used to create consistent, partial-thickness defects in rabbit and other large animals with minimal surgical training and that can facilitate pre-clinical testing of lamellar and in situ-forming biosynthetic matrix materials for corneal repair. Materials & Methods: In this study, three modified trephines were designed to create deep corneal wound defects with consistent depth in large animals. The modified trephines incorporated either 3D-printed parts made from photopolymerizable resins, or custom-cut commercially available Teflon sheets. Wound defects were imaged with optical coherence tomography (OCT), and the depth was analyzed based on the OCT images. Results: The results revealed that an inner-stopper guard trephine had the best performance in creating consistent and precise wound defect depth compared to modified vacuum trephine and custom guard vacuum trephine. A 75% ± 10% cut of the cornea was achieved with the inner-stopper guard trephine. The wound defect depth by created by the inner-stopper guard trephine was independent of the corneal thickness or size of the globes. Although the cut depth of the inner-stopper guard trephine differed by the experience-level of its users, the consistency (standard deviation) of the depth was independent of experience. Conclusions: Our studies provided three cost-efficient animal trephines that can create corneal wounds of consistent depth by lab researchers without extensive training in keratectomy.